ANALYSIS OF THE HIERARCHY OF NEEDS AND STRIVING FOR SUPERIORITY IN THE MOVIE 500 DAYS OF SUMMER - Prasetyo, Ananda Gusti Yudhi; Lestari, Indah (Universitas Gunadarma, 2024)
This research delves into the manifestation of Abraham Maslow's hierarchy of needs and the factors driving striving for superiority, as exemplified by Tom Hansen in the movie 500 Days of Summer. Employing a qualitative methodology, the study analyzes dialogue and monologue data from the film to explore how Tom Hansen embodies Maslow's hierarchy of needs and exhibits factors related to striving for superiority. The findings reveal that Tom Hansen manifests all levels of needs outlined by Maslow, while also demonstrating factors indicative of striving for superiority. Specifically, the analysis identifies 35 instances related to Maslow's Hierarchy of Needs, encompassing physiological needs, safety needs, love and belongingness, esteem needs, and self-actualization. Additionally, 12 instances are identified concerning striving for superiority, including the pursuit of a final goal, striving force as compensation, personal superiority, and striving for success.